If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 5 = 61 Reorder the terms: 5 + 3x = 61 Solving 5 + 3x = 61 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 3x = 61 + -5 Combine like terms: 5 + -5 = 0 0 + 3x = 61 + -5 3x = 61 + -5 Combine like terms: 61 + -5 = 56 3x = 56 Divide each side by '3'. x = 18.66666667 Simplifying x = 18.66666667
| 4(3b-1)+6=5(b+4) | | 15a*15a+ab-6b*6b-2a*2a-5ab-2a*2a+4ab+b*b= | | 80=4(2x-3)+20 | | x(2x+1)=19 | | 6n-4=3n+8 | | 8x+11-3x=46 | | x-4/4-1=x-12/5 | | 1/2x-5=5/8x | | 4(5x+10)-16x+8=40 | | a+12-3a+4a-30= | | p*p-p*p*p*p-p*p*p+2p*2p*2p+4p*4p*4p*4p-3p*3p+3p*3p= | | x^2+0.03x-0.91=0 | | (12-x)(x+1)(x-1)=160 | | in(x)+in(2-x)=0 | | b/8-6=10 | | 7x-5=10+2x | | (100-10)*c=45 | | 5(8x-6)=34 | | y^2+100=0 | | -2(9x-7)+12=8 | | a/2+5=11 | | 100-10*c=100 | | 10+x=32-4 | | 3a+8b+7a-b= | | 15x-8-10x+6=53 | | 6g=17 | | 7x+4(3-5x)=0 | | 4m+7=51 | | 18y*18y-18y-16y*16y+12y-15= | | Y=2x128/52 | | 2(3x-4)=3x+25 | | 5x+13=-5(2+2x)-8x |